2010
DOI: 10.1002/num.20480
|View full text |Cite
|
Sign up to set email alerts
|

Homotopy perturbation method for homogeneous Smoluchowsk's equation

Abstract: In this work, homotopy perturbation method (HPM) has been used to solve homogeneous Smoluchowski's equation. The results will be compared with Adomian decomposition method (ADM). It is shown that the results of the HPM are the same as those obtained by ADM. To illustrate the reliability of the method, some special cases of the equation have been solved as examples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…This equation is widely applied to describe the time evolution of the cluster-size distribution during aggregation processes. In this paper, the following Smoluchowski's equation [5,6], will be considered; ( , ) ( ) ( ), , ,…”
Section: Homogeneous Smoluchowski Coagulation Equationmentioning
confidence: 99%
“…This equation is widely applied to describe the time evolution of the cluster-size distribution during aggregation processes. In this paper, the following Smoluchowski's equation [5,6], will be considered; ( , ) ( ) ( ), , ,…”
Section: Homogeneous Smoluchowski Coagulation Equationmentioning
confidence: 99%
“…Homotopy perturbation method was used to find the exact or the approximate solutions of the linear and nonlinear integral equations [16,18], the two-dimensional integral equations [19][20][21], and the integrodifferential equations [22][23][24][25]. This method enables seeking a solution of the following operator equation:…”
Section: The Solution Of Two-phase Inverse Stefan Problemmentioning
confidence: 99%
“…In this section, the homotopy perturbation method is applied to solve the inverse problem. We make the homotopy map for (22):…”
Section: The Solution Of the Two-phase Inverse Stefan Problemmentioning
confidence: 99%
“…Later, He (1999b, 2003, 2020b) introduced another method called homotopy perturbation method (HPM) to solve PDEs which convert the results into the form of a series. Many authors (Biazar et al , 2010; Biazar and Ghazvini, 2009; Taşcan and Özer, 2010) applied this technique and showed that HPM is an excellent technique which converges to the exact solution very rapidly. Khan and Wu (2011) showed that HPM is an efficient tool for nonlinear equations using He’s polynomials.…”
Section: Introductionmentioning
confidence: 99%